Penerapan Computational Thinking Pada Materi Percabangan Dan Perulangan Untuk Menyelesaikan Permasalahan Sman5 Pekanbaru - ibnu surya; Rika Perdana Sari; Silvana Rasio Henim; Puja Hanifah (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2022)
The thought process needed to formulate problems and solutions so that these solutions can become effective information processing agents in solving problems is called computational thinking (CT). The process of implementing learning using the CT approach is related to those provided by Google for Education, namely abstraction, algorithm design, decomposition, and pattern recognition. CT is a term that refers to the main ideas and concepts in the fields of informatics and computer science, so the proposed Community Service (PkM) activity this time will introduce looping and branching materials. Learning is taught and presented in a fun way, and then activities are carried out that discuss the problems that exist around the students of SMAN 5 Pekanbaru. It is hoped that by injecting the CT concept it can foster students' creativity, foster a culture of information, algorithms, and computational thinking, and involve students in utilizing information technology, computers, and applications from an early age